The 25-Year War : America's Military Role in Vietnam - Palmer, Bruce, Jr., 1913-2000 (Book collections on Project MUSE., 2014)
"" On April 30, 1975, Saigon and the government of South Vietnam fell to the communist regime of North Vietnam, ending -- for American military forces -- exactly twenty-five year of courageous but unavailing struggle. This is not the story of how America became embroiled in a conflict in a small country half-way around the globe, nor of why our armed forces remained there so long after the futility of our efforts became obvious to many. It is the story of what went wrong there militarily, and why. The author is a professional soldier who experienced the Vietnam war in the field and in the h